Characterisation of PP2Cβ in regulating tumour suppressor pathways in cancer cell lines : A thesis presented to Massey University in partial fulfilment of the requirement for the degree of Masters in Genetics - Miller, Rachel Elizabeth (Massey University, 2016)
Tumour suppressor p53 is a key regulator in preventing neoplastic transformation by inducing cell cycle arrest or death in response to stress-signalling pathways. Consequently, p53 is often non-functional during the early stages of cancer development through either direct mutation or aberrant expression of negative regulators. PP2Cβ is a protein phosphatase which was recently identified as a negative regulator of p53 and cellular senescence. However, the function of PP2Cβ in cancer development is not fully understood. The aim of this study was to characterise PP2Cβ and its regulation of p53 pathways in human cancer cell lines. This aim was split into two objectives. The first objective was to examine the effects of PP2Cβ on p53 pathways and cell proliferation in four cancer cell lines with various genetic backgrounds. A protein analysis using western immunoblotting procedures indicates that p53 pathways are activated in cell lines expressing wildtype p53 and Ras. Consistent with activated p53 pathways, PP2Cβ knockdown significantly reduced proliferation rates, which could be attributed to an increased expression of a p53 target gene, p21 cell cycle inhibitor. The second objective was to investigate the mechanisms regulating of PP2Cβ gene expression. Previously, p63 was identified as a potential negative regulator of PP2Cβ gene expression based on a modular relational database that integrated microarray results with a genome-wide search of p53 family member response elements. It was therefore hypothesized that p63 could negatively regulate PP2C gene expression. Mammalian expression vectors carrying either the p63 or p73 expression cassette were constructed and PP2Cβ expression was analysed upon overexpression of p53 family members (p53, p63 and p73) in two human cancer cell lines. A reverse-transcriptase coupled quantitative PCR showed that overexpression of p63 resulted in decreased PP2Cβ expression in p53 wildtype cell line. Taken together the results presented here suggest that restoration of tumour suppressors such as p53 and Rb activity by PP2C inhibition could be used as a potential therapeutic strategy in cancer treatment.
Keywords: Research Subject Categories::MEDICINE::Dermatology and venerology,clinical genetics, internal medicine::Clinical genetics::Medical genetics